Governança em parques científicos tecnológicos brasileiros - SAMPAIO FILHO, Milton Correia (2015)
The situation of Brazilian STPs in operation led to field research. Even with the stimulus of public policy and support of associations, nothing has been mapped on the disclosure of the primary or secondary outcomes. Empirical research field, for his exploratory concerned to ensure its replication for recording the criteria for selecting the multiple cases and the interactive search details with triangulation of data collected. Three STPs (TECNOPUC, UNICAMP and SergipeTec) indicated another five (Valetec - Novo Hamburgo, Tecnosinos - Sao Leopoldo, Parque do Rio, CIATEC, TECHNOPARK) to participate in the interactive survey of triangulation of data collected through semi-structured qualitative interviews, analysis documents and on-site observations. The conclusions developed by field research in response to the problem – How governance happen in brazilian scientific technological parks? - contribute to present a reflection on governance in brazilian scientific technological parks, general purpose of the research. Empirical research also has shown that the lack of effectiveness of governance (no qualitative or quantitative performance indicators to measure it) is possible cause tensions between the dominant instrumental rationality in governance guidelines and the substantive rationality present in practice the same. Tensions are characterized by elements such as heterogeneity in characteristics of the organizations that make up the STP, lack of consensus on common goals, pressure forces and influences that affect the trusts, non-compliance standards and personal and organizational preferences. The characteristics of the governance of STPs are related to its origin. This contribution adds value to the criteria mapped in theory: number of participants, geographic reach and time of existence. Leadership relations championed by the government and / or companies can negatively influence the STP's performance as a whole. There is the perception of the main participants on the customization as a factor adding (or disruptive) value, depending on the integration of cognitive, social and emotional skills aligned with socially recognized values.